Degradation of 2-Chlokophenol in Water Using Advanced Oxidation Processes - Leong, Jin Hoong (2005)
The presence of endocrine disruptor chemicals (EDCs) in treated wastewater lately, is alarming. Chlorophenols, an endocrine disruptor chemical compound is hardly eliminated in water using conventional treatment. In this study, contaminated water containing 2-Chlorophenol was treated using the Advanced Oxidation Processes (AOPs) reactor (anolyte solution/ozone/UV) and anolyte solution alone. Various conditions such as initial pH values, ozone dosages, reaction time and initial 2- Chlorophenol concentrations were tested to achieve the optimum degradation of 2- Chlorophenol. Possible intermediates and by-products in each treatment effluents were investigated. Results showed that almost 90% of 2-Chlorophenol (5mgIL) degraded in water with initial alkaline pH values (11-12) using AOPs reactor (anolyte solution (O.4L)/Ozone 50% (0.5 1 mg/L)/UV). Complete (1 00%) degradation of 2-Chlorophenol in ı.ater was achieved when initial concentration of 2-Chlorophenol was 0.04 mg/L in neutral pH condition. On the other hand, at least 70% of the ZChlorophenol degraded when treated with anolyte solution in all initial pH values and initial 2-Chlorophenol concentrations. Complete (100%) degradation of 2-Chlorophenol occurred when the initial concentration of 2-Chlorophenol was 1.0 mg/L in original pH condition. All effluent samples had acidic pH value except those 2-Chlorophenol solutions with initial alkaline pH values. Comparison between two treatments showed that anolyte solution was more effective to degrade 2-Chlorophenol than AOPs reactor at original and neutral pH conditions. The degradation of 2-Chlorophenol compounds in water was achieved up to 100% using anolyte solution compared to the AOPs reactor at higher 2- Chlorophenol concentration in most cases. The 2-Chlorophenol degraded intermediates and by-products using AOPs reactor and anolyte solution were mainly alkenes, alkanes, carboxylic acid, ketones and ether functional group compounds.